Career Motivation Activities Guide, 4th through 6th Grade - Toledo Public Schools, OH.; Toledo Public Schools, OH. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
The activities guide is intended primarily to assist teachers in grades 4-7 in teaching career awareness concepts. Instructional activities correlate basic skill and career education objectives. The 29 units cover topics related to social studies (self-awareness, the community, the school, transportation, the environment, family roles, economic concepts, advertising, and politics) and science (nutrition, food production, and physiological functions). Material from the fields of art, language, math, and home economics is also incorporated into the units. The final chapter presents career awareness activities and materials for special students in multiple grade levels. Topics include family roles, the rewards of work, accepting emotions, manners, and salaries. Each unit contains the following: grade level designation, area of interest, subject area, title, developmental and behavioral objectives, concepts, activities, media and materials, and evaluative comments by teachers who have previously used the unit. Materials listed are filmstrips, possible class speakers and topics, demonstration paraphernalia, classroom equipment, children's books, study prints, and miscellaneous materials used in the activities. Supplementary materials include grooming pointers, information on selling oneself to an employer, personal data sheet, and a sample employment form. (Author/DB)
ERIC Note: Best copy available.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Activity Units; Affective Objectives; Career Awareness; Career Development; Career Education; Career Guidance; Career Planning; Curriculum Guides; Decision Making; Educational Objectives; Elementary Education; Goal Orientation; Grade 4.; Grade 5.; Grade 6.; Grade 7.; Interdisciplinary Approach; Language Arts; Learning Activities; Sciences; Self Concept; Skill Development; Social Studies; Special Education; Student Motivation; Units of Study; Guides, General